2016
DOI: 10.1371/journal.pone.0158297
|View full text |Cite
|
Sign up to set email alerts
|

Pegylated Interferon α-2a Triggers NK-Cell Functionality and Specific T-Cell Responses in Patients with Chronic HBV Infection without HBsAg Seroconversion

Abstract: Pegylated interferon α-2a (Peg-IFN-α) represents a therapeutic alternative to the prolonged use of nucleos(t)ide analog (NA) in chronic hepatitis B (CHB) infection. The mechanisms leading to a positive clinical outcome remain unclear. As immune responses are critical for virus control, we investigated the effects of Peg-IFN-α on both innate and adaptive immunity, and related it to the clinical evolution. The phenotypic and functional features of the dendritic cells (DCs), natural killer (NK) cells and HBV-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 38 publications
1
17
0
Order By: Relevance
“…In this study, we found an increase in CD56 bright NK cells during Peg-IFN-α-2b treatment (with or without ADV), which is in agreement with the Peg-IFN-α-2a-induced expansion of activated CD56 bright NK cells21. This is similar to the observed effect of IFNα therapy in HCV or HDV infection2223.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found an increase in CD56 bright NK cells during Peg-IFN-α-2b treatment (with or without ADV), which is in agreement with the Peg-IFN-α-2a-induced expansion of activated CD56 bright NK cells21. This is similar to the observed effect of IFNα therapy in HCV or HDV infection2223.…”
Section: Discussionsupporting
confidence: 89%
“…Noteworthy, in our study, Peg‐IFN was added to an effective antiviral therapy with TDF and to patients with a long‐term controlled HBV replication; nevertheless, the activation of peripheral iNKT cells might reflect their activity in liver tissue where these cells are more abundant and might represent a critical component of the complex immune response against HBV. Indeed, if long‐term therapy with NA partially restores the adaptive immunity, interferon‐α through a pleiotropic immunomodulating action may stimulate also the innate immune system, that is needed to achieve HBV replication control including nuclear cccDNA, and achieving HBsAg loss/anti‐HBs seroconversion …”
Section: Discussionmentioning
confidence: 99%
“…10,11 Our results also showed that CHB patients compared apy with NA partially restores the adaptive immunity, interferonα through a pleiotropic immunomodulating action may stimulate also the innate immune system, that is needed to achieve HBV replication control including nuclear cccDNA, and achieving HBsAg loss/anti-HBs seroconversion. 45 Several caveats in the experimental design of the present study must be acknowledged that include the small number of patients enrolled in the add-on arm that might have lowered the power of statistical analyses. Second, the add-on group had a statistically significant lower median age compared to NA group; this finding could have influenced the immunological results, although we did not confirm the association between age and iNKT/γδ T cells in our cohort.…”
Section: Quencies Of Circulating Inkt Cells With High Interindividualmentioning
confidence: 98%
“…[85][86][87][88] Addition of Peg-IFNα, in a cohort of patients virally suppressed on NAs, induced the activation of DC's, expansion of CD56 bright NK cells and increased the frequency of Th1/Th17-orientated HBVspecific T cells. 93 Notably, these effects were not associated with improved clinical outcomes. Viral load reduction is able to maintain the immune stimulatory effects of Peg-IFNα, when administered in combination or sequence, compared to Peg-IFNα alone, which implies there may be beneficial outcomes with add-on or combination therapies.…”
Section: Nucleos(t)ide Analoguesmentioning
confidence: 97%
“…Addition of Peg‐IFNα, in a cohort of patients virally suppressed on NAs, induced the activation of DC's, expansion of CD56 bright NK cells and increased the frequency of Th1/Th17‐orientated HBV‐specific T cells . Notably, these effects were not associated with improved clinical outcomes.…”
Section: Viral and Immune Aspects Of Therapymentioning
confidence: 98%